Optimized layout of supporting facilities in mountainous industrial parks: a case study of Chongqing Dadi Industrial Park - Duan, Ran; Tang, Rui; Wang, Zhigang; Yang, Jiyi; Su, Jiafu (Frontiers in Ecology and Evolution, 2023)
Industrial parks play a pivotal role in driving urban economic growth in China, particularly in light of the country's extensive mountainous terrain. Effective arrangement of supporting facilities within these parks is crucial for steering industries towards high-quality development. However, the intricate topography of mountainous regions presents challenges in devising optimal layouts for these facilities. This article adopts a user-centric perspective to investigate the impact of mountainous terrain on user fatigue within industrial parks. We employ equivalent coefficient methods to establish a correlation between undulating paths in mountainous terrain and flat paths. This correlation serves as the foundation for a visual analytical tool designed to facilitate the rational placement of supporting facilities in mountainous industrial parks. To validate our approach, we conduct an empirical analysis of the supporting facility layout at Chongqing Dadi Industrial Park. The insights gleaned from our study provide a basis for optimizing the placement of supporting facilities in mountainous industrial parks, enhancing user experiences and aligning with urban growth trajectories. In conclusion, our research offers dual benefits: firstly, it provides a scientific framework for guiding the rational layout of supporting facilities in mountainous industrial parks, addressing the challenges posed by complex terrain. Secondly, it offers practical insights into the comprehensive planning and design of these parks, promoting sustainable urban and economic growth. Our research thus emerges as a valuable resource for the advancement and optimization of mountainous industrial parks in China.